Mapping the Intellectual Structure and Collaboration Landscape of Space Sustainability Research - Aswathy, S.; Sandhya, P. S.; Ajayalal, P. R. (Journal of Information and Knowledge, 2025)
This study examines the development of space sustainability research from 1960 to 2025 using data from the OpenAlex database. Scientometric methods were applied to map the field’s intellectual structure through co-citation analysis, identify key topics via keyword co-occurrence, and classify research themes using a thematic map. A three-field plot (authors-keywords-sources) highlights influential contributors and publication trends, while a word cloud reveals high-frequency terms. The study also explores global research patterns through country and institutional collaboration networks, offering insights into the field’s thematic focus and international partnerships.